2018
DOI: 10.3168/jds.2017-13201
|View full text |Cite
|
Sign up to set email alerts
|

The effects of L-type amino acid transporter 1 on milk protein synthesis in mammary glands of dairy cows

Abstract: The mammary gland requires the uptake of AA for milk protein synthesis during lactation. The L-type amino acid transporter 1 (LAT1, encoded by SLC7A5), found in many different types of mammalian cells, is indispensable as a transporter of essential AA to maintain cell growth and protein synthesis. However, the function of LAT1 in regulating milk protein synthesis in the mammary gland of the dairy cow remains largely unknown. For the current study, we characterized the relationship between LAT1 expression and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…23 Moreover, recent studies have indicated that the regulation of protein translation and cell proliferation by amino acids and hormones via the mTOR signalling pathway is a crucial determinant of milk production in BMECs. 15,16,24 In accordance with these previous reports, and based on our data that U2AF65 regulates milk synthesis and cellular growth and controls the mRNA expression of mTOR and subsequent mTOR phosphorylation, we propose that U2AF65 regulates milk synthesis and cell growth via mTOR signalling. We observed that mTOR protein levels were relatively stable in cells overexpressing U2AF65 or transfected FIGURE 4 Effects of U2AF65 overexpression and knockdown on the mTOR and SREBP-1c signalling protein by splicing.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…23 Moreover, recent studies have indicated that the regulation of protein translation and cell proliferation by amino acids and hormones via the mTOR signalling pathway is a crucial determinant of milk production in BMECs. 15,16,24 In accordance with these previous reports, and based on our data that U2AF65 regulates milk synthesis and cellular growth and controls the mRNA expression of mTOR and subsequent mTOR phosphorylation, we propose that U2AF65 regulates milk synthesis and cell growth via mTOR signalling. We observed that mTOR protein levels were relatively stable in cells overexpressing U2AF65 or transfected FIGURE 4 Effects of U2AF65 overexpression and knockdown on the mTOR and SREBP-1c signalling protein by splicing.…”
Section: Discussionsupporting
confidence: 91%
“…BMECs treated with amino acids and hormones showed higher U2AF65 expression than that of the control group ( Figure 1C and 1D). 15,16 The above findings suggested that expression of U2AF65 responded to extracellular stimuli, such as amino acids and hormones and might be involved in the regulation of milk synthesis in BMECs. 15,16 The above findings suggested that expression of U2AF65 responded to extracellular stimuli, such as amino acids and hormones and might be involved in the regulation of milk synthesis in BMECs.…”
Section: Amino Acids and Hormones Induce U2af65 Expression In Bmecsmentioning
confidence: 87%
See 3 more Smart Citations